2013
DOI: 10.1115/1.4024115
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Leading-Edge Bumps in the Control of Stall Onset in Axial Fan Blades

Abstract: Taking a lead from the humpback whale flukes, characterized by a series of bumps that result in a sinusoidal-like leading edge, this paper reports on a three-dimensional numerical study of sinusoidal leading edges on cambered airfoil profiles. The turbulent flow around the cambered airfoil with the sinusoidal leading edge was computed at different angles of attack with the open source solver OpenFOAM, using two different eddy viscosity models integrated to the wall. The reported research focused on the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 17 publications
5
56
0
Order By: Relevance
“…Subsequent numerical simulations also confirmed the finding through higher-fidelity numerical methods [16,17,18,19,20]. These were accompanied by experiments on both full-and semi-span rectangular planforms in either wind [21,8,22] or water tunnels [23].…”
Section: Introductionsupporting
confidence: 62%
“…Subsequent numerical simulations also confirmed the finding through higher-fidelity numerical methods [16,17,18,19,20]. These were accompanied by experiments on both full-and semi-span rectangular planforms in either wind [21,8,22] or water tunnels [23].…”
Section: Introductionsupporting
confidence: 62%
“…In the case of the TLE wing, it stalled at 14°or 15°. Post-stall simulations for AoA 20°showed that the TLE wings outperformed Corsini et al [75] studied the effect of TLE on symmetric NACA 0015 and cambered NACA 4415 airfoils. 3D numerical investigation was carried out using Open FOAM.…”
Section: Numerical Studymentioning
confidence: 96%
“…An assessment of the modified geometry on a cambered airfoil entailed the comparison of aerodynamic performance against the same geometry without a sinusoidal-shaped leading edge, as well as an uncambered airfoil. The sinusoidal-shaped leading edge modified the aerofoil lift coefficient during stall, with an early recovery of the aerofoil's aerodynamic work capability and a 30% gain in lift after stall for the WHALE4415 airfoil [43].…”
Section: Baselinementioning
confidence: 98%
“…Recently, Corsini et al [43] presented a particular fan blade crenulation that they associated with humpback whales' abihty to execute very sharp rolls and loops under water. The crenulations were in the form of bumps on the leading edge of the whale's flukes.…”
Section: Baselinementioning
confidence: 98%